STUDY ON SITUATION AND RESULTS OF TREATMENT OF ACUTE HEART FAILURE IN PATIENTS WITH ST-ELEVATION MYOCARDIAL INFARCTION AT LONG KHANH REGIONAL GENERAL HOSPITAL - Chí Trung, Võ; Hữu Dũng, Thân; Mạnh Hoàng, Nguyễn (Journal of Health and Aging, 2025)
Heart failure after acute myocardial infarction (MI) is a common complication and increases mortality. The factors influencing heart failure and the treatment outcomes of acute heart failure following acute MI remain unclear. This study aim to determining the prevalence, associated factors, and treatment outcomes of acute heart failure in patients with ST-elevation MI. A case series descriptive study was conducted on 110 patients with ST-elevation MI undergoing percutaneous coronary intervention at Long Khanh Regional General Hospital from June 2023 to June 2024. Results showed the prevalance of acute heart failure is 35%. Factors associated with acute heart failure after MI included: late hospital admission >12 hours (OR = 13.6; 95% CI: 1.8–100.8); double-vessel coronary artery disease (OR = 8.87; 95% CI: 1.0002–78.65), triple-vessel coronary artery disease (OR = 10.06; 95% CI: 1.11–90.77), and left main coronary artery disease (OR = 37.4; 95% CI: 1.8–763.2). Treatment outcomes included average hospital stay of 7.9 ± 5.2 days; the most frequently intervened coronary branch was the RCA; pre-intervention coronary flow was mostly TIMI 0, and post-intervention normal coronary flow was achieved in 86% of cases. Common complications were access-site hematoma, fever, and infection; in-hospital mortality rate was 7%; procedural success rate was 83.6%. These findings emphasize the importance of early identification of prognostic factors that can easily lead to acute heart failure after myocardial infarction, in order to improve approaches and patient outcomes